Peritoneal hepatoid carcinoma with chemotherapy response and possible stem cell involvement - Christine K.C. Loo; Suzanne Danieletto; Michael Friedlander; Michael A. Pearen; Grant A. Ramm (Elsevier, 2018)
Hepatoid carcinoma is a rare type of malignancy showing hepatocellular differentiation, without tumour in the liver. Hepatoid carcinoma in the female genital tract of older patients has been suggested to be a rare type of yolk sac tumour, possibly derived from a somatic tumour. However, the mechanisms causing a somatic tumour to show hepatoid or yolk sac tumour differentiation are unknown. We present a case report of peritoneal hepatoid carcinoma with immunohistochemical evidence of stem cells and hepatic stellate cells in this tumour, which have not been previously reported. We compare morphological features in our case of hepatoid carcinoma with reported findings in hepatoid yolk sac tumour and hepatocellular carcinoma and discuss the possible histogenesis of this tumour and findings suggestive of tumour stroma interactions, using information from our observations and correlating this with results reported from animal experiments, human developmental studies and other reports of hepatoid carcinoma.